KERJASAMA PEMERINTAH DESA PASAR BARU PANGEAN DENGAN CAMAT DALAM MENUNTASKAN KEMISKINAN DI KECAMATAN PANGEAN MELALUI PROGRAM KELUARGA HARAPAN (PKH) TAHUN 2016 - Taufik Widiya Saputra; M.Y.Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research entitled "Cooperation of Village Government Pasar Baru Pangean With Camat In Completing Poverty In Pangean Sub District Through Family Hope Program (PKH) Year 2016". This research is based on the cooperation between the Village Government and the Camat in solving the existing poverty in Pasar Baru Pangean Village through Family Hope Program (PKH) launched by the Ministry of Social Affairs to reduce the poverty index. The formulation of the problem in this research is how the cooperation of the Village Government of Pasar Baru Pangean with Camat in completing poverty through Family Hope Program (PKH) in Pangean Subdistrict and also the implementation of Family Hope Program (PKH) in Pangean Subdistrict. The problems that exist in this research is to know the form of cooperation between Village Government of Pasar Baru Pangean and Camat in solving the poverty found in Pasar Baru Pangean Village and want to know the implementation of Family Hope Program (PKH) Program in Kecamatan Pangean. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were in-depth interviews, documentation and observation, while other required data came from research informants and supported by supporting documents related to this research.Based on the results of research that has been done show that there are three forms in cooperation Village Government Market New Pangean with Camat in poverty alleviation through family program harrapan (PKH) in 2016 that is 1. Coordination Shape, which coordination is done in two ways that is directly and indirectly, 2.The form of Data Collection to encourage the synchronization of data every year, and 3.Bentuk Pembinaan by the Camat to the Village Government Pasar Baru Pangean with the form of facilitating the guidance of PKH activities in 2016. Implementation of family planning program (PKH) found in Pangean sub-district in 2016 generally has no significant obstacles. There is only a problem with margins of data error in population resuscitation. The data is not always accurate or not always 100% true, there must be a mistake, because 100% accurate data is god's data as well as changes in economic status to the community.Keyword: Cooperation, Poverty Alleviation, PKH Implementation